Occurrence, formation mechanism, and health risk of polycyclic aromatic hydrocarbons in barbecued food - Wei Du; Su Jiang; Yali Lei; Jinze Wang; Zhanpeng Cui; Ping Xiang; Zhaofeng Chang; Wenyan Duan; Guofeng Shen; Yiming Qin; Bo Pan; Yunjiang Yu (Ecotoxicology and Environmental Safety)
Polycyclic aromatic hydrocarbons (PAHs) show negative impacts on human health. Dietary intake is the predominant way for PAH exposure, of which barbecued food is a crucial contributor. This review aims to provide a comprehensive insight into the formation mechanism, influencing factors, mitigation strategies, and health risks of PAHs in barbecued food. PAHs in barbecued food are formed by Hydrogen abstraction and acetylene addition (HACA) mechanism, Diels-Alder reaction and Maillard reaction, which was influenced by heat source, temperature, cooking time, and the meat type. There are significant differences in PAH concentrations in different barbecued foods, where chrysene dominates among the selected PAH species. To reduce PAHs formation, adding marinades and adopting alternative cooking methods are suggested, which effectively reduce PAH levels by 53 −89 %. In addition, it is estimated that people in countries such as Pakistan has an incremental lifetime cancer risk (ILCR) over 10−5 via barbecued food consumption, indicating potential health risk. This work highlighted that regular monitoring of PAH levels in barbecued food and dynamic modification of relevant safety limits are recommended to ensure food safety.